Basic life support knowledge in a war-torn country: a survey of nurses in Yemen - Sameer A. Alkubati; Christopher McClean; Rebecca Yu; Bander Albagawi; Salman H. Alsaqri; Mohammed Alsabri (BMC, 2022)
Abstract Background Successful implementation of Basic life support (BLS) is critical to improving survival rates and outcomes, especially among healthcare workers. To our knowledge, there is no available literature pertaining to the level of BLS knowledge of health care professionals in Yemen. Methods Data was collected for this cross-sectional descriptive study from June to August 2020, using a 10-item questionnaire related to cardiopulmonary resuscitation (CPR) and BLS, along with questions on socio-demographic characteristics. Participants were nurses in public and private hospitals located in Al-Rahida and Al-dimna cities, Taiz governance and Hodeidah city, Hodeidah governance in Yemen. Results Out of 220 distributed questionnaires, 200 were returned with a response rate of 90.9%. More than a half (53.65%) of answer choices for BLS knowledge were correct. There was a significant difference in knowledge score based on level of education where those who had Bachelor degree had more knowledge (P = 0.000). Those who said they had received training in CPR or received information about CPR had significantly higher scores than those who did not receive (P = 0.000). Conclusions BLS knowledge among nurses in Yemen is below an acceptable level to ensure maximum survival in the event of cardiac arrest. Disseminating BLS information and training in a cost effective and efficient manner will provide a large benefit in terms of lives saved with minimal costs.